STATUS KESEHATAN MASYARAKAT DAN KUALITAS LINGKUNGAN PADA DAS GARANG KABUPATEN DAN KOTA SEMARANG (Studi Analisis Spasial Pada daerah Urban, Rural, Pantai, Pegunungan) - Sulistiyani - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
Program need information and data for planning, evaluation and monitoring. But much data never to do analysis, example service based  data from Health  Center. The aim of this research is to know public  health statue and environment quality at DAS  Garang in Semarang City and Regency with spasial analysis from urban, rurel, seashore,mountain range. The Results of this research show that dominant factor of environment is  water  especially microbiologt. Health  Statuei in Urban that is ARI, Diarrhea, Dysentry, Skin and  Eye for group of>60 years. In  Rural far group of 0-4  years old : ARI, Diarrheo, Skin and Eye. In seashore area ARI, Skin and Eye for group of >60 years.ln  Mountain  ronge is  ARI,  Diarrhea, Skin and  Eye for group of 0-  4 years old.